Análise dos fatores motivacionais dos gestores e administradores de fundos mútuos de investimentos - Gasparelo, Luiz Eduardo (2012)
The aim of this study is to raise and assess the main factors in the motivation of professionals who provide services related to management, administration and custody of mutual funds, using a descriptive research based on characteristics of a representative sample of these professionals in the city of Sao Paulo. The survey was developed from epistemologically validated methodology, driven to the sample recognized in the professional area (certified professionals ANBIMA) and their responses were compiled into a multidimensional matrix to evaluate the explanatory variables related to the level of motivation of professionals, including their remuneration level. It was concluded that, despite the importance given by these professionals to remuneration and reward for performance, several other factors are equally or more relevant, even showing that motivational factors of such professionals are dynamic and subject to alternations related to their career success